What we talk about when we talk about leadership in South Sudan. Issue 1 (2nd January 2020) - Masua, David; Mowles, Chris; Sarra, Nicholas
ABSTRACT: It is important to think critically about how we develop leaders, particularly in highly unpredictable countries like South Sudan. This article gives an account of a yearlong reflective and experiential programme in Juba which sought to straddle the paradox of outside and inside: it took seriously the critical insight that leadership development needs to take greater account of endogenous experience. However, to do so we drew on methods developed elsewhere, but which prioritise local experience. The programme focused on the everyday interdependencies of group life, rather than an abstract and often idealised understanding of leadership favoured in many business schools.